A Corporate Scandal that Hits Close to Home: Examining Owners' Responses to the Volkswagen Diesel Emissions Scandal. Issue 6 (2nd November 2017) - Markowitz, Ezra M.; Chapman, Daniel A.; Guckian, Meaghan L.; Lickel, Brian
ABSTRACT: The 2015 Volkswagen Group (VW) diesel emissions scandal has affected no group of individuals more directly than owners of the affected vehicles. Yet to date no research has examined in depth how owners have responded to the scandal. This includes not only what owners have already done or plan to do with their vehicles (e.g. repair, participate in the buyback programme) but also their interpersonal communicative actions (e.g. talking with other owners) and attitudinal reactions (e.g. perceptions of the VW-EPA settlement). We conducted two surveys—one prior to and one after a settlement was reached between VW and US regulators—to examine owners' behavioural and attitudinal responses. Here we present descriptive, topline results from these surveys, which reveal relatively strong but heterogeneous owner engagement with the scandal. Owners report significant ambivalence about their own and VW's mitigative options moving forward. Given the role owners will play in mitigating the environmental and health impacts of the scandal, understanding their responses is of critical importance.